Functional conduction system mapping in sheep reveals Purkinje spikes in the free wall of the right ventricular outflow tract - Blok, Michiel; den Ouden, Bram L.; Kuiper, Marion; Ophelders, Daan R. M. G.; Jongbloed, Monique R. M.; Zeemering, Stef; Jensen, Bjarke; van Hunnik, Arne; Boukens, Bastiaan J. (Frontiers in Physiology, 2025)
Ablation of sites displaying Purkinje activity is highly effective against idiopathic ventricular fibrillation which often originates in the right ventricular outflow tract. However, during endocardial mapping Purkinje potentials are rarely, if never, detected in the right ventricular outflow tract. In the present study, we aimed to determine whether the Purkinje system extends into the right ventricular outflow tract. Hearts of five female sheep were blood-perfused in a Langendorff setup in which we performed epicardial and endocardial voltage mapping. During atrial pacing, the right ventricular outflow tract epicardium activated later than the epicardium of the left and right ventricular free walls. Endocardial mapping revealed Purkinje spikes at several sites in the free wall of the right ventricular outflow tract. In one heart, Purkinje spikes preceded ventricular premature beats during mapping, but were not visible during sinus rhythm. Subsequent immuno-histological examination showed a network of Connexin 40-positive Purkinje fibers across and within the wall of the right ventricular outflow tract. Quantitative analysis revealed that the transmural Purkinje fiber network was more abundant near the endocardium than epicardium. In conclusion, the Purkinje system extends into the right ventricular outflow tract of the sheep heart. These findings demonstrate that the sheep could be a valuable model for studying Purkinje-related arrhythmias in the right ventricular outflow tract.